The components of student\'s professional responsibilities in the process of clinical education: A scoping review - fatemeh keshmiri; Khadijeh Nasiriani (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: Recognition of the professional role and responsibility is a key component in successfully playing professional roles. The present study aimed to recognition of the components of students' professional responsibilities in the process of clinical education. Materials & Methods: This is a scoping review study. This study searched, databases including Science Direct, Magiran, Web of Science, PubMed, and Google Scholar by keywords of professional responsibility, professional behavior, clinical education, and student. Results: 3821 articles were studied and monitored step by step and finally 44 articles were selected. The evaluation of articles based on content analysis was categorized into six categories and 33 subcategories. The six categories include educational tasks, patient care, communication skills and information exchange, personal development, professional development, and observing professionalism and ethics. Conclusion: In this study, the components and dimensions affecting the student's professional responsibilities in the education process were extracted. The results could be used in planning educational interventions to improve the professional responsibility of students in clinical education and also to the development of student assessment tool